2020
DOI: 10.1021/acs.jpcc.0c00204
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Cu–S Motif Transformation and Au4 Distortion via Thiol Ligand Exchange Engineering

Abstract: Au 4 Cu 4 (SAdm) 5 (Dppm) 2 ]Br and [Au 4 Cu 5 (C 6 H 11 S) 6 (Dppm) 2 ](BPh 4 ) (SAdmH = 1-adamantane mercaptan, C 10 H 15 SH; C 6 H 11 SH = cyclohexyl mercaptan; Dppm = bis-(diphenylphosphino)methane, Ph 2 PCH 2 PPh 2 ), which was well characterized by single-crystal X-ray crystallography (SCXC) and monitored by time-dependent UV−vis absorption spectroscopy. Surprisingly, by etching with cyclohexyl mercaptan (C 6 H 12 S), [Au 4 Cu 4 (SAdm) 5 (Dppm) 2 ] + was converted to [Au 4 Cu 5 (C 6 H 11 S) 6 (Dppm) 2 ] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 38 publications
1
20
0
Order By: Relevance
“…In terms of the electrochemical properties, the HOMO–LUMO gaps in NCs are primarily determined by the size and structure of nanocluster. , The electrochemical measurements were carried out for [Au 5 Cu 6 (Dppf) 2 (SAdm) 6 ] + . Figure represented the DPV behavior of it.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of the electrochemical properties, the HOMO–LUMO gaps in NCs are primarily determined by the size and structure of nanocluster. , The electrochemical measurements were carried out for [Au 5 Cu 6 (Dppf) 2 (SAdm) 6 ] + . Figure represented the DPV behavior of it.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the ligand and the overall framework affect the overall stability of the cluster. ,, The time-dependent UV–vis spectra of [Au 4 Cu 4 (SAdm) 5 (Dppm) 2 ]Br and [Au 4 Cu 5 (C 6 H 11 S) 6 (Dppm) 2 ]­(BPh 4 ) indicated that both nanoclusters were not stable in CH 2 Cl 2 solution at room temperature (Figure ). Dissolved in the DCM, the solution of [Au 5 Cu 6 (Dppf) 2 (SAdm) 6 ]­(BPh 4 ) can remain green, and the optical spectra clearly display the characteristic absorption peaks of [Au 5 Cu 6 (Dppf) 2 (SAdm) 6 ]­(BPh 4 ) after 80 h. The solid state can be stably stored at room temperature for more than 0.5 year (Figure S6).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrospray ionization mass spectra (ESI‐MS) is often performed to analyse transformation mechanism for ligand exchange induced size transformation, such as thiol ligand‐induced transformation of Au 38 (SC 2 H 4 Ph) 24 to Au 36 (SPh‐ t Bu) 24 [7,11] . Compared with studies on thiol ligands as exchange ligands, [7,12,13] fewer studies on phosphine ligands as inducers to reconstruct clusters are reported, let alone studies on bisphosphine ligands [14] . How does the bisphosphine ligand reconstruct the surface structures of the nanoclusters, especially for alloy clusters [15]…”
Section: Figurementioning
confidence: 99%
“…nanoclusters was successfully synthesized according to our previous report. [32] The UV-vis absorption spectrum showed that the final product exhibited three peaks centered at 440, 500, and 580 nm, respectively (Figure 1a). The final product was further analyzed by electrospray ionization mass spectrometry (ESI-MS).…”
Section: Introductionmentioning
confidence: 99%